Responsabilidad social empresarial una visión integral (Corporate social responsibility an integral vision) - Abreu Quintero, José Luis; Cruz Álvarez, Jesús Gerardo (Facultad de Contaduría Pública y Administración U.A.N.L., 2011)
Abstract. The historical origin of the corporate social responsibility concept is established in the ancient Persian civilization and an analysis of the concept evolution is carried out, bringing out a debate on the diverse actual definitions, from a perspective of recognized researchers including the approach of an extensive diversity of institutions at the international level, making emphasis in the latinamerican approximation. An own concept is concluded founded in the existence of an universal consciousness that should contemplate the balance among society, nature and corporate profitability.